A review on soft computing techniques in automated negotiation - Jazayeriy, Hamid; Azmi Murad, Masrah Azrifah; Sulaiman, Md. Nasir; Udzir, Nur Izura (Academic Journals, 2011)
Automated negotiation offers new capability for buyers and sellers to efficiently trade goods and services in online markets. In high-dimensional real world negotiations, many agents may communicate with each other over multi-issue products. In this paper, we review soft-computing techniques used in e-negotiation. Although implementation of real world negotiations is very hard but using soft computing techniques can lead us to a suitable approximation in automated negotiation. Using a combination of soft computing techniques can decrease the complexity of high-dimensional negotiation.